Determinant Employee Engagement and Their Impact on Millennial Generation Employees Performance at Life Insurance Companies in DKI Jakarta - Silvia, Nabella; Rifzaldi, Nuraeni; Sulaeman, Suhendar; Yusuf, M. (Dinasti Publisher, 2024)
Employee engagement plays a crucial role in enhancing organizational performance, particularly among the millennial workforce. This study aims to investigate the determinants of employee engagement and its impact on millennial generation employee performance in life insurance companies in DKI Jakarta. The research methodology involves a quantitative approach using structured questionnaires distributed among employees. Data analysis includes descriptive statistics, correlation analysis, and regression analysis. The findings reveal significant positive relationships between work-life balance, flexible working arrangements, employee engagement, and employee performance. Furthermore, employee engagement is found to mediate the relationship between work-life balance/flexible working arrangement and employee performance. These results underscore the importance of fostering employee engagement and implementing work-life balance and flexible working arrangements to enhance millennial employee performance in life insurance companies. These results emphasize the significance of work-life balance, flexible working arrangements, and employee engagement in enhancing millennial employee performance in life insurance companies in DKI Jakarta.